Folk dance and sedentary lifestyle in adolescents in the quarantine period - Dávila Tamayo, Pablo Damián; Cabezas Mejía, Edison Damián; Nasimba Suntaxi, Cristina Maribel; Sandoval Jaramillo, María Lorena (mktDESCUBRE; Vol 1 No 18 (2021): Eighteenth Edition (July - December), 2021)
Today humanity has a common public health concern and the Government has arranged for the population to stay in their homes; Given this reality, a large number of studies have identified the benefits that Recreation provides to reduce sedentary lifestyle in people. For this reason, the research focuses its attention on evaluating a recreational program of folk dance as a means of reducing sedentary lifestyle in quarantine aimed at second-year high school students of the Gran Colombia Educational Unit in Quito. The project is based on documentary, field and quasi-experimental research designs, through the application of standardized tests that made it possible to collect primary data that contributed significantly to establish diagnoses; Product of these investigative processes was reached to establish the final conclusion that responds to the general objective; In this sense, consequence of the analysis of two samples selected from a longitudinal study, it is concluded that there is a significant difference in the measurements before and after the treatment; obtaining a biliteral significance of 0.000010 which is less than or equal to the alpha value of 0.05; Values that force reject the null hypothesis, accepting the alternative hypothesis. Therefore, it is confirmed that the Folk Dance Recreational Program has significant effects in reducing sedentary lifestyle in times of quarantine in second-year high school students from the Gran Colombia.